Feasibility of and barriers to thalassemia screening in migrant populations: a cross-sectional study of Myanmar and Cambodian migrants in Thailand - Julia Z. Xu; Wilaslak Tanongsaksakul; Thidarat Suksangpleng; Supachai Ekwattanakit; Suchada Riolueang; Marilyn J. Telen; Vip Viprakasit (BMC, 2021)
Abstract Background Thalassemia, an inherited hemoglobin disorder, has become a global public health problem due to population migration. Evidence-based strategies for thalassemia prevention in migrants are lacking. We characterized barriers to thalassemia screening and the burden of thalassemia in migrant workers in Thailand. Methods Multilingual demographic and KAP surveys were completed by 197 Thai, 119 Myanmar, and 176 Cambodian adults residing in Thailand. Thalassemia awareness, socio-demographic predictors, and knowledge and attitude scores were compared between migrant and Thai subjects. Comprehensive thalassemia testing was performed for migrants. Results Migrants had extremely poor thalassemia awareness (4.1%) compared to Thai subjects (79.6%) and had lower thalassemia knowledge scores but similar attitude scores. Surveys identified differing sociodemographic factors predicting awareness in Thai and migrant subjects, as well as key misconceptions likely to hinder thalassemia screening uptake. Nearly all migrants consented to thalassemia testing. We identified abnormal hemoglobin profiles in 52.7% of migrants and a higher projected rate of severe thalassemia births in migrants. Conclusions The high burden of thalassemia and tremendous knowledge gap in migrants needs urgent attention. Thalassemia screening was feasible and acceptable in our migrant population. Sociocultural and structural barriers merit further attention when designing thalassemia screening and prevention policies for migrants in Thailand and globally.